Secrets of eclectic places spanning the centuries (2010)
Flier for 'the tenth annual architectural tour of the Monday Club.' Houses on the tour include the Burch House, the Payne House, the Leopold Building, the Sauer-Adams Adobe, the Vetterline House, the Oliver House, and the Johnson Cottages.